SAT0248 Chromosome 1Q31 variant is associated with ankylosing spondylitis only in the presence of clinically significant bowel symptoms. (23rd January 2014) - Roberts, R.L.; Jenks, K.; Merriman, T.R.; Highton, J.; Harrison, A.; Stebbings, S.
Abstract : Background: Clinical and genetic data suggests that the aetiology of both Crohn's disease (CD) and Ankylosing spondylitis (AS) is centred in the gut and that these diseases share immunopathogenic pathways related to gut inflammation. Results from a recent study identified 18 genetic loci which shared an association with both CD and AS [1] . The strongest shared association with AS was noted for a chr 1q31 single nucleotide polymorphism (SNP, rs11584383 ) in high linkage disequilibrium with SNPs in the kinesin Family Member 21B gene (p=1.0e-10, OR=0.74, 95% CI 0.68-0.82) [1] . Objectives: The purpose of this study was to test for association of CD loci in AS patients stratified according to the presence of clinically significant bowel symptoms. Methods: A longitudinal, population-based study of axial spondyloarthritis in New Zealand has recruited 144 patients to date. Participants completed the Dudley Inflammatory Bowel Symptom questionnaire (DISQ) [2] a 15 item self-reporting questionnaire recently validated for assessing bowel symptoms in AS [2] . Patients with AS and 524 matched controls were genotyped for 9 CD-associated single nucleotide polymorphisms (SNPs) ( IL23R rs11209026, rs1343151, rs10489630 ; IL12B rs10045431 ; CDKAL1 rs6908425; JAK2 rs10758669 ; LRRK2/MUC19 rs11175593; STAT3 rs744166 ; 1q32 rs11584383 ) using TaqMan assays. Genotypic and haplotypic chi-square testing was performed using the software PLINK. Our cohort had 60% power to detect an association with the 1p31 SNP rs11584383 and 20-25% power to detect an association with the other SNPs (α=0.05). Results: The minor allele of 1q32 SNP rs11584383 conferred significant protection against AS in our New Zealand cohort (p=0.002, OR=0.62, 95% CI 0.45-0.84). This association was lost once patients with clinically significant bowel symptoms (DISQ score ≥11 out of 60) [2] were excluded (p=0.180). A protective effect was detected for an IL23R haplotype comprising the minor alleles of the SNPs rs10489630 and rs11209026 (p=0.021, OR=40, 95% CI 0.18-0.89). This haplotype is rare therefore we did not stratify by DISQ score. None of the other SNPs tested showed any evidence of association with AS. Conclusions: The significant protective effects of 1q31 SNP rs11584383 and IL23R SNPs rs10489630 and rs11209026 against AS observed in our cohort are consistent with previous reports in AS [1] and CD. The lack of association detected for other SNPs is most likely due to our currently modest number of AS patients. Stratification of rs11584383 genotype using DISQ scores to identify patients with bowel inflammation provides preliminary evidence that association of CD loci may only be observed in AS patients with clinically significant bowel symptoms. References: Danoy P et al. 2010. PLoS Genetics 6(12):1-5. Stebbings S et al. 2011. Rheumatology (Oxford) (in press) Disclosure of Interest: None Declared